دراسة مؤشرات توافر الغذاء وأثرها على قياس الأمن الغذائي في الجزائر - خلايفه صدام حسين; سلامي أحمد (جامعة الوادي University Of Eloued, 2024)
تحاول هذه الدراسة البحث في اهم مؤشرات قياس توافر الغذاء وعلاقتها بالأمن الغذائي في الجزائر، حيث تم تطبيق المنهج الوصفي التحليلي لمؤشرات الدراسة على الجزائر للفترة 2000-2019، وتوصلت الدراسة الى أن أغلب مؤشرات توافر الغذاء في الجزائر لا تزال بعيدة عن المستوى المطلوب والمحدد من المنظمات العالمية رغم وجود تحسن في بعض منها كمؤشر انتاج الغذاء ومتوسط امدادات الطاقة الغذائية، وهو ما يمكننا من اعتماد مؤشرات توافر الغذاء للحكم على مستوى الامن الغذائي الجزائري، والذي يبقى تحدي تحقيقه مرهون بوضع استراتيجيات وخطط فعالة من طرف الدولة لتساهم في تحقيق الامن الغذائي للجزائر. This study attempts to investigate the most important indicators of measuring food availability and its relationship to food security in Algeria, where the descriptive analytical approach of the study indicators was applied to Algeria for the period 2000-2019, and the study found that most of the indicators of food availability in Algeria are still far from the required level set by international organizations, despite the improvement in some of them, such as the index of food production and the average food energy supply, which enables us to adopt food availability indicators to judge the level of Algerian food security, which remains a challenge to achieve depends on the development of effective strategies and plans by the state to contribute to achieving food security food of Algeria
Study of food availability indicators and their impact on measuring food security in Algeria
Keywords: الأمن غذائي; توافر الغذاء; المؤشرات; Food security; Food availability; Indicators